2020
DOI: 10.1039/c9ra09776g
|View full text |Cite
|
Sign up to set email alerts
|

Cembrane-type diterpenoids from the gum resin of Boswellia carterii and their biological activities

Abstract: Cembrane-type diterpenoids from the gum resin of Boswellia carterii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…20 In another case, the main components of frankincense oil by steam distillation contains mono-, sesqui-, di-, and tri-terpenoids, with anti-inflammatory, cytotoxic, hepatoprotective, antibacterial, and antifungal activities. 21,22 However, the main components of FVO in this study are cembrane- and cembrene C, with a total content of about 61%. Cembrane-type diterpenoids are a class of terpene with a 14-membered oxygenated macrocycle consisting of four isoprenoid units, with higher bioactivities.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…20 In another case, the main components of frankincense oil by steam distillation contains mono-, sesqui-, di-, and tri-terpenoids, with anti-inflammatory, cytotoxic, hepatoprotective, antibacterial, and antifungal activities. 21,22 However, the main components of FVO in this study are cembrane- and cembrene C, with a total content of about 61%. Cembrane-type diterpenoids are a class of terpene with a 14-membered oxygenated macrocycle consisting of four isoprenoid units, with higher bioactivities.…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that there are abundant alkaloids, flavonoids, terpenoids, tannins and phenols in the methanol extract of frankincense, where the content of mastic acid accounts for 37%, showing anti‐inflammatory and anti‐aging effects 20 . In another case, the main components of frankincense oil by steam distillation contains mono‐, sesqui‐, di‐, and tri‐terpenoids, with anti‐inflammatory, cytotoxic, hepatoprotective, antibacterial, and antifungal activities 21,22 . However, the main components of FVO in this study are cembrane‐type diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…AKBA also chemosensitized cancer cells toward cisplatin and gemcitabine treatment (79,82). Compounds other than AKBA have been investigated, but their anti-proliferative properties have been studied at higher concentrations, making them less effective (79,(84)(85). Boswellia extracts and isolated components, especially AKBA, are also able to inhibit tumor growth in vivo (79).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Baghel et al (2012) found that kaempferol can control cancer, and quercetin showed antioxidant and anticarcinogenic activities. Sun et al (2020) isolated a new eight active compounds from the gum resin of Boswellia carterii as mainly as cembrane-type diterpenoids and they found that these compounds have many activities like anti-inflammatory with (IC 50 of 14.8 µM), cytotoxic with (IC 50 > 100 µM), and hepatoprotective with (IC 50 > 30 µM). Alyahya & Asad (2020) found that Boswellia sacra extract does not possess any toxic effect on the testis, revealed its antioxidant potential that may protect testes against the effect of toxicants.…”
Section: Cytotoxicity and Antitumor Activity Of Frankincense Powder On Human Cell Linesmentioning
confidence: 99%